Strategic atlas: A comparative geopolitics of the world's powers - Gérard Chaliand (Harper-Collins, 1992)
The book lets we see the world not only from the American and European points of view, but also from the perspective of the Commonwealth of Independent States, China, Latin America, Africa and the Middle East, including up-to-date information on Kuwait and the Persian Gulf region, the reunification of Germany, the Commonwealth of Independent States and the newly independent nations of the former Soviet Union, Central and Eastern Europe's troupe spots, the European Economic Community. The clear and attractive maps and charts present all the factors that affect international relations - population, ethnic conflict, natural resources, proximity of unfriendly powers